Anomalous Hall effect in noncollinear antiferromagnetic Mn 3NiN thin films - Cohen,L; Boldrin,D (Physical Review Materials, 2019)
We have studied the anomalous Hall effect (AHE) in strained thin lms of the frustrated anti-ferromagnet Mn3NiN. The AHE does not follow the conventional relationships with magnetizationor longitudinal conductivity and is enhanced relative to that expected from the magnetization inthe antiferromagnetic state belowTN= 260 K. This enhancement is consistent with origins fromthe non-collinear antiferromagnetic structure, as the latter is closely related to that found in Mn3Irand Mn3Pt where a large AHE is induced by the Berry curvature. As the Berry phase inducedAHE should scale with spin-orbit coupling, yet larger AHE may be found in other members of thechemically exible Mn3AN structure.